Pengaruh Emosi dan Mood Terhadap Motivasi Belajar Mahasiswa (Studi pada Mahasiswa Program Studi Manajemen Universitas Muhammadiyah Bandung Angkatan 2023) - Sastradireja, Dhafin Al-Rasyid; Kurniawan, Aris; Priatna, Elky Rimba; Nurhakim, Reihan Ahmad; Nurasiah, Sofa Parihah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the influence of emotions and mood on the learning motivation of 2023 cohort students in the Management Study Program at Universitas Muhammadiyah Bandung. A quantitative approach with a causal-associative research design was employed. The sample consisted of 82 respondents selected through simple random sampling from a population of 200 students. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using IBM SPSS Statistics. The findings reveal that emotions have a positive and significant effect on learning motivation (t = 2.502; p = 0.014), while mood also has a positive and significant effect (t = 2.956; p = 0.004). Simultaneously, emotions and mood significantly influence learning motivation (F = 13.073; p < 0.001). The coefficient of determination (R²) of 0.249 indicates that both variables explain 24.9% of the variance in students' learning motivation. These findings support the Affective Events Theory, which suggests that affective conditions play an important role in shaping individual behavior and motivation. Therefore, higher education institutions should foster a supportive learning environment that promotes positive emotional conditions to enhance students' learning motivation.